2021
DOI: 10.15388/infedu.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Abstraction in Computer Science Education: An Overview

Abstract: When we "think like a computer scientist," we are able to systematically solve problems in different fields, create software applications that support various needs, and design artefacts that model complex systems. Abstraction is a soft skill embedded in all those endeavours, being a main cornerstone of computational thinking. Our overview of abstraction is intended to be not so much systematic as thought provoking, inviting the reader to (re)think abstraction from different -and perhaps unusual -perspectives.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…The results showed that in literature review researchers mention about abstraction but it can not been seen that the studies which focuses on abstraction are missing. Mirolo (2022) had some suggestion on studying abstraction with different student groups.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that in literature review researchers mention about abstraction but it can not been seen that the studies which focuses on abstraction are missing. Mirolo (2022) had some suggestion on studying abstraction with different student groups.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Abstraction is considered as an element in the context of computer science, as well as a process in the cognitive context. During abstraction, many thinking processes work in cognition (Mirolo, 2022). In this manner one of the important ability for the process of abstraction is reasoning (Duncan, 2013;Kramer, 2007).…”
Section: Research Problemmentioning
confidence: 99%
“…While conducting research into differentiated assessments, especially when using the type of questions examined by Nelson et al (2020), it is important to take abstraction into account due to the complexity in the questions. The role of abstraction in CS education is broadly acknowledged (Mirolo et al, 2021;Aharoni, 2000). However, this is a complex "soft concept" that is hard to define formally, and which is difficult to characterize in this context, making it difficult to understand how to teach and assess it (Hazzan, 2008).…”
Section: Prerequisite Skills and Abstractionmentioning
confidence: 99%
“…As discussed in Section 2.3, it is worth connecting these middle-ground skills to abstraction skills, which are notoriously difficult to teach and assess (Mirolo et al, 2021). In particular, they align well with the higher levels of the hierarchy proposed by Perrenet et al (2005) and the operational dimensions of Statter and Armoni (2020), since they require understanding the code at a higher level, as understanding what the program does for some particular input is not enough.…”
Section: Differentiated Assessmentmentioning
confidence: 99%
“…So, experiments, good experiences and educative proposals in compiler education are very important. Moreover, literature reviews reveal the importance of studying multiple semiotic representations and different abstraction levels in computer science [7], and in algorithmic thinking [8, sec. 2.3].…”
Section: Introductionmentioning
confidence: 99%